A novel photocleavable heparin derivative with light controllable anticoagulant activity. (15th March 2018) - Sun, Feifei; Liu, Yinyin; Wang, Dongdong; Wang, Zhaojie; Mu, Haibo; Wang, Feng; Ding, Kan; Duan, Jinyou
Graphical abstract: Highlights: A photocaged derivative of heparin (HP) was synthesized. The caged HP has low-anticoagulant activity compared with HP. The caged HP can release carboxyl groups upon UV to exert anticoagulant activity. The caged HP and products irradiated by UV were nontoxic to HaCaT cells. Abstract: Heparin (HP) has enormous potential for clinical medication applications owing to its anticoagulant activity. However, the strong anticoagulant capacity of HP also leads to some side effects. Herein, a photocaged derivative (HP-DMNB) of HP was synthesized for light control of its anticoagulant activity. The synthesized HP-DMNB was characterized by NMR and FTIR analysis, which confirmed the successful modification of HP with the photocleavable 4, 5-dimethoxyl-2-nitrobenzyl (DMNB) groups. After the modification, the molecular weight of HP-DMNB (DS = 0.34%) changed from 61 to 71 kDa. Anticoagulant activity analysis showed that HP-DMNB had a reduced anticoagulant capacity compared with commercial HP, while its anticoagulant activity will regain after releasing the free carboxyl groups of HP under UV light. In addition, HP-DMNB and its UV irradiated products were observed to possess good biocompatibility through the MTT assays and live-dead assays with HaCaT cells, which may have impacts on the clinical medication applications of HP.